Thermally enhanced frequency upconversion in Nd3+-doped fluoroindate glass - Menezes, L. de S.; Maciel, G. S.; Araújo, Cid B. de; Messaddeq, Younes [UNESP] (AIP Publishing, 2001)
Multiphonon assisted frequency upconversion was observed in a Nd3+-doped fluoroindate glass pumped at 866 nm. A near-infrared upconverted emission at 750 nm with a peculiar linear dependence with the laser intensity was observed and explained. The intensity of the upconverted emission experienced a 40-fold enhancement when the sample's temperature was varied from 298 to 498 K. A rate equation model that includes light pumping and multiphonon absorption via thermally coupled electronic excited states of Nd3+ was used, describing quite well the experimental results. © 2001 American Institute of Physics.